Dropout among Perpetrators of Intimate Partner Violence Attending an Intervention Program - Cunha, Olga Cecília Soares da (2022)
Batterer intervention programs (BIPs) are one of the most relevant strategies to reduce intimate partner violence (IPV). However, the rates of dropout are significantly high, which may impact the effectiveness of such strategies. Literature has identified several factors associated with BIP dropout; nonetheless findings remain inconsistent. The aims of this study were to analyze the differences between perpetrators who completed the program and those who droped out, in terms of sociodemographic, violence-related and intrapersonal variables, as well as identify the predictors of dropout. 83 IPV perpetrators completed a set of measures that assessed attitudes toward domestic violence, physical and psychological abuse of a partner, aggression, coping skills, and readiness to change. Variables related to past criminal history and sociodemographics were also colletected. 42.2% of IPV perpetrators failed to complete the intervention program. The results revealed that age and previous convictions by other crimes than IPV discriminated perpetrators who completed the program from those who droped out, such that, being young and having a previous conviction predicted dropout. These findings reveal a need to further analyze the impact of these factors so BIPs can be tailored to meet the specificities of IPV perpetrators and prevent treatment dropout.